Effectiveness of Scoliosis Specific Exercises in Improving Cobb's Angle-A Systematic Review and Meta-Analysis - Malik W A Majoka; Sohail Rasool; Sheikh Muhammad Ebad Ali; Omer Islam; Maleeha; Muhammad Osama Siddiqui; Fatima Shahid (ziauddin University, 2024)
Background: Scoliosis is defined as a Three-dimensional deformity that can be diagnosed by measuring the spinal curves. For measuring the curvature, we employ Cobb's method to calculate Cobb's angle on the anteroposterior radiograph of the spine. The commonest type of scoliosis is adolescent idiopathic scoliosis (AIS) that is seen in adolescent females. Our literature research revealed a scarcity of systematic reviews regarding the role of Scoliosis specific exercises (SSE) in reducing Cobb's angle in scoliosis. This review of the literature evaluates the role of SSE compared to the standard treatment practices in reducing Cobb's angle in scoliosis patients. Methods: The literature was scrutinized according to PRISMA guidelines where PubMed, Google Scholar, and Cochrane Library were searched for randomized controlled trials in the English language with the search words "Cobb's angle", "physiotherapy", "outcomes", "scoliosis specific exercises", "correction of" and "scoliosis" in different combinations published between 2016 to 2022. One group i.e. interventional group consisted of SSE with standard care while the other group i.e. control group did not receive SSE. Mean ± SD was used to measure the change in Cobb's angle. The difference was pooled by standardized mean difference (SMD) into forest plots. The risk of bias was assessed by the Oxford quality scoring system (OQSS). Results: The SMD was pooled from five studies where SMD remained -0.717 (-1.142, -0.291) (CI=95%, p-value< 0.05) between the intervention and control group. Heterogeneity by the I2 test was reported to be moderate and non-significant (I2 = 52.42%, p-value>0.05) Conclusion: We concluded that SSE produced a decrease in Cobb's angle compared to the group without SSE. However, good quality randomized controlled trials with larger sample sizes and longer follow-ups are needed to strengthen the role of SSE. Keywords: Low Angle Scattering, Physical Therapy Modalities, Scoliosis.